LEGAL ORGANIZATION OF THE WORK OF PERSONS DEPRIVED OF LIBERTY IN SERBIA (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
In Serbia, there are several categories of persons deprived of their liberty,which for the time while they are in a penal institution have certain rightsand obligations. Thus, in penal institutions, the sentence of imprisonment,which was pronounced in the criminal, as well as in the misdemeanorprocedure, is served. The penalty of juvenile imprisonment shall beexecuted in the penitentiary institution for juveniles. The educationalmeasure of referral to a correctional home is executed in a JuvenileCorrectional Facility in Krusevac. In penitentiary institutions is alsoexecuted the punishment of supletory prison, as also as detention. For allpersons is a common, and that is that they are deprived of their liberty,and their treatment while deprived of their liberty differ.The subject of the author's work is the work of persons deprived of theirliberty, that is, their legal order in the Republic of Serbia. The aim of thework is to see how the legislator has regulated the working engagement ofpersons deprived of liberty, but also to see how the sub-legal acts furtherregulate this area. The current regulations governing the workingengagement of persons deprived of their liberty will be critically analyzed.